2017
DOI: 10.5483/bmbrep.2017.50.8.128
|View full text |Cite
|
Sign up to set email alerts
|

RING E3 ligases: key regulatory elements are involved in abiotic stress responses in plants

Abstract: Plants are constantly exposed to a variety of abiotic stresses, such as drought, heat, cold, flood, and salinity. To survive under such unfavorable conditions, plants have evolutionarily developed their own resistant-mechanisms. For several decades, many studies have clarified specific stress response pathways of plants through various molecular and genetic studies. In particular, it was recently discovered that ubiquitin proteasome system (UPS), a regulatory mechanism for protein turn over, is greatly involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…In addition, some E3 ubiquitin ligases regulate abiotic stress response, including drought tolerance [ 9 , 14 , 15 , 16 , 17 ]. XERICO (Greek for ‘drought tolerant’) from Arabidopsis has been shown to confer drought tolerance when overexpressed in Arabidopsis [ 18 ] and rice [ 19 ] through the increase of endogenous ABA level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some E3 ubiquitin ligases regulate abiotic stress response, including drought tolerance [ 9 , 14 , 15 , 16 , 17 ]. XERICO (Greek for ‘drought tolerant’) from Arabidopsis has been shown to confer drought tolerance when overexpressed in Arabidopsis [ 18 ] and rice [ 19 ] through the increase of endogenous ABA level.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Saccharomyces cerevisiae , which has 47 RING-type E3 encoding genes, rice and Arabidopsis contain 378 and 499 genes, respectively (Kraft et al, 2005; Stone et al, 2005; Mazzucotelli et al, 2006; Li et al, 2008; Du et al, 2009). Recent studies have revealed the cellular roles of RING E3 Ub ligases in response to abiotic stress in the dicot model plant Arabidopsis (Cho et al, 2017; Stone, 2018). In contrast, our knowledge concerning the roles of RING E3 ligases in the monocot cereal rice in response to abiotic stresses is relatively rudimentary.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the negative regulation on ABA pathway by DDA1 is related to the structural stabilization of C4E3 by interacting with DCAFs needs further studies. Similarly, most U-box E3 ubiquitin ligases negatively regulate the ABA pathway [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Contrary to C4E3, many RING-type E3 ubiquitin ligases positively regulate the ABA pathway [ 56 , 60 ].…”
Section: Discussionmentioning
confidence: 99%